Optimizing Students’ Creative Thinking Skills on the Pythagorean Theorem: A Deep Learning-Based Teaching Module Integrated with Local Culture - Izwita Dewi; Hasratuddin; Ade Andriani; Nurhasanah Siregar (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2026)
A persistent challenge in mathematics education is students limited creative thinking ability. This study aims to examine the effectiveness of a learning module in enhancing students’ creative thinking skills. A one-group pretest–posttest design was employed, involving 32 eighth-grade students from a junior high school in Medan, Indonesia. The instruments included pretest and posttest measures of creative thinking ability, observation sheets documenting the implementation of the learning process, and a learning module integrating deep learning principles with local cultural elements. Data were analyzed using paired-sample t-tests for normally distributed data and Wilcoxon signed-rank tests for non-normally distributed data. The results indicate a significant improvement in students’ creative thinking abilities following the implementation of the module, with a notably large effect size observed among male students (Cohen’s d = 4.12). This finding suggests the presence of individual differences in learning responses; however, it should be interpreted with caution, as gender was not the primary focus of the study. Accordingly, further research is recommended to investigate the role of gender in deep learning–based instruction, particularly when integrated with local cultural contexts